Production of bio-oil rich in acetic acid and phenol from fast pyrolysis of palm residues using a fluidized bed reactor: Influence of activated carbons. (November 2016) - Jeong, Jae-Yong; Lee, Uen-Do; Chang, Won-Seok; Jeong, Soo-Hwa
Highlights: Palm residues with activated carbons were pyrolyzed in a bench-scale (3 kg/h) fast pyrolysis plant. Coal-derived activated carbon had positive influence on the formation of phenol. Aqueous phase of bio-oils was mostly comprised of acetic acid and water. Viscous phase of bio-oils appeared to be available to the phenolic resin synthesis. Abstract: In this study, palm residues were pyrolyzed in a bench-scale (3 kg/h) fast pyrolysis plant equipped with a fluidized bed reactor and bio-oil separation system for the production of bio-oil rich in acetic acid and phenol. Pyrolysis experiments were performed to investigate the effects of reaction temperature and the types and amounts of activated carbon on the bio-oil composition. The maximum bio-oil yield obtained was approximately 47 wt% at a reaction temperature of 515 °C. The main compounds produced from the bio-oils were acetic acid, hydroxyacetone, phenol, and phenolic compounds such as cresol, xylenol, and pyrocatechol. When coal-derived activated carbon was applied, the acetic acid and phenol yields in the bio-oils reached 21 and 19 wt%, respectively. Finally, bio-oils rich in acetic acid and phenol could be produced separately by using an in situ bio-oil separation system and activated carbon as an additive.